Dysregulated circRNA_100876 contributes to proliferation and metastasis of colorectal cancer by targeting microRNA-516b (miR-516b). Issue 8 (2nd August 2020) - Zhang, Jianrong; Wang, Huaiming; Wu, Ketong; Zhan, Fajie; Zeng, Huan
ABSTRACT: Colorectal cancer (CRC) is globally one of the most common malignant tumors. Increasing number of studies indicate that circular RNAs (circRNAs) play a significant role in the initiation and progression of CRC. However, the role of circRNA_100876 in CRC progression remains unclear. In this study, we investigated the expression and function of circRNA_100876 in CRC progression. The expression of circRNA_100876 and microRNA-516b (miR-516b) was compared in normal and CRC tissues using quantitative real-time polymerase chain reaction (RT-qPCR). In addition, proliferation, metastasis, and apoptosis of the cells were analyzed using Cell Counting Kit-8 (CCK-8) assay, Transwell assay, and flow cytometry, respectively. The relationship between circRNA_100876 and miR-516b was further verified using dual-luciferase reporter assay. Our data showed that circRNA_100876 was highly expressed in CRC tumor tissues, and the high expression gtransition (EMT)-related proteins. Furthermore, we found that the addition of miR-516b reversed the anti-tumor effect induced by the downregulation of circRNA_100876. In conclusion, this study revealed that circRNA_100876 is overexpressed in CRC tissues and represents a promising therapeutic target for CRC.